Evidence of Truly Young High-α Dwarf Stars - Yuxi(Lucy) Lu; Isabel L. Colman; Maryum Sayeed; Louis Amard; Sven Buder; Catherine Manea; Soichiro Hattori; Marc H. Pinsonneault; Adrian M. Price-Whelan; Megan Bedell; David Nidever; Jennifer A. Johnson; et al. (The Astronomical Journal)
The existence of high- α stars with inferred ages <6 Gyr has been confirmed recently with large spectroscopic and photometric surveys. However, stellar mergers or binary interactions can induce properties associated with young ages, such as high mass, rapid rotation, or high activity, even in old populations. Literature studies have confirmed that at least some of these apparently young stars are old merger products. However, none have ruled out the possibility of genuinely young high- α stars. Because cool GKM dwarfs spin down, rapid rotation can be used to indicate youth. In this paper, we provide strong evidence that truly young high- α stars exist by studying high- α rotators in the Kepler and K2 field with abundance measurements from GALAH and APOGEE. After excluding close binaries using radial velocity (RV) measurements from Gaia DR3 and multiepoch RVs from APOGEE, we find a total of 32 high- α rapid rotators with periods ∼10–30 days, 14 of which have lithium measurements from GALAH, indicating that they have not gone through past mass transfer or stellar merger events. We identify 10 young high- α candidates with no signs of merger-induced mixing or close companions. One clear example is a G dwarf with a measurable rotation and an age of < 5 Gyr that is likely a single star with multiple RV measurements from APOGEE, has significant lithium detection from GALAH ( A (Li) = 1.79), and has no signs of planet engulfment.